(PENGARUH PEMBELAJARAN OUTING CLASS PADA MERDEKA BELAJAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA MATA PELAJARAN BAHASA INDONESIA KELAS V SD INPRES TAMALATEA KABUPATEN GOWA) - Ayu Lestari (STKIP Subang, 2023)
This research is research related to the influence of outing class learning on independent learning to improve students' descriptive essay writing skills in class V of SD Inpres Tamalatea, Gowa Regency. The aim of this research is to describe student learning outcomes and determine the influence of out-of-class learning methods on the descriptive essay writing skills of class V students at SD Inpres Tamalatea. This research used a one group pretest-posttest design research design with a population of all class V students at SD Inpres Tamalatea where the sampling technique used was a saturated sampling technique. The research instruments used were descriptive essay writing skills tests and observation sheets. The data analysis technique used is descriptive statistics and inferential statistics using the t-test. The results of this research show that before learning was implemented outside of grade 12, students had low descriptive essay writing skills with scores that were still below the KKM with insufficient qualifications. After being given treatment, the students' skills and grades increased until they were above the KKM score with Very Good Category Qualifications. Based on the research results, it shows that the alternative hypothesis (Ha) is accepted. At a significance level of 5%, the t_table value is 2.201, so when compared with the calculated t_value of 30.08, the null hypothesis (H_0) is rejected. This means that the learning method outside the classroom (outing class) has an effect on improving students' descriptive essay writing skills at a significance level of 5%.